2022
DOI: 10.1186/s12951-022-01620-5
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional mesoporous silica-cerium oxide nanozymes facilitate miR129 delivery for high-quality healing of radiation-induced skin injury

Abstract: Radiation-induced skin injury (RISI) is an important challenge for clinical treatments. The main causes of RISI include hypoxia in the wound microenvironment, reactive oxygen species (ROS) activation, and downregulation of DNA repair proteins. Here, a multiple radioresistance strategy was designed for microRNA therapy and attenuating hypoxia. A novel mesoporous silica (MS) firmly anchored and dispersed cerium (IV) oxide (CeO2) nanoparticles to form MS-CeO2 nanocomposites, which exhibit superior activity in inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
(51 reference statements)
0
5
0
1
Order By: Relevance
“…These data are consistent with the authors’ earlier data on the antioxidant properties of CeO 2 nanoparticles, which showed that, at the concentration of 10 −5 M, they were able to effectively reduce the generation of radiation-induced hydrogen peroxide [ 30 ]. The redox properties of nanoceria enables it to work as a scavenger of reactive oxygen species (ROS) and free radicals, preventing the development of radiation-induced damage to cells, organs, and whole organisms [ 31 , 32 , 33 , 34 , 35 ]. It has previously been shown that nanoceria is capable of inactivating a wide range of radicals and ROSs, including the hydroxyl radical [ 36 ], nitroxyl radical [ 37 ], singlet oxygen [ 38 ], and superoxide anion radical [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with the authors’ earlier data on the antioxidant properties of CeO 2 nanoparticles, which showed that, at the concentration of 10 −5 M, they were able to effectively reduce the generation of radiation-induced hydrogen peroxide [ 30 ]. The redox properties of nanoceria enables it to work as a scavenger of reactive oxygen species (ROS) and free radicals, preventing the development of radiation-induced damage to cells, organs, and whole organisms [ 31 , 32 , 33 , 34 , 35 ]. It has previously been shown that nanoceria is capable of inactivating a wide range of radicals and ROSs, including the hydroxyl radical [ 36 ], nitroxyl radical [ 37 ], singlet oxygen [ 38 ], and superoxide anion radical [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanotherapeutic approaches have recently demonstrated significant efficacy in addressing RISI [ 244 ]. In a recent approach, microRNA therapy employed in the mesoporous silica (MS)-nCe composites was designed to resolve the radiation-induced ROS [ 245 ]. These nanocomposites could counteract radiation-induced ROS and HIF-1α activation that leads to enhanced healing in radiation-induced wounds.…”
Section: Therapeutic Efficacy Of Nz@hydrogels In Clinically Relevant ...mentioning
confidence: 99%
“…1438 Furthermore, SiO 2 has been reported as a carrier to load nanozymes, natural antioxidants and drugs for relieving inflammation-related radiation-induced skin injury, ischemic stroke and rheumatoid arthritis. 47,1439,1440 Besides, simple loading fulfilling the respective functions of carriers and anti-inflammatory materials, silicon-based materials can also reinforce their own properties through antioxidants. For instance, Zhang et al integrated CeO 2 in BG to co-construct 3D printed scaffolds, in which CeO 2 not only scavenged ROS to eliminate inflammation and promoted mineral deposition for cell proliferation and osteogenic differentiation, but also enhanced the mechanical properties of BG to support new tissue in-growth (Fig.…”
Section: Regenerative Medicinementioning
confidence: 99%